Indiana Jones and the Temple of Doom [videorecording (DVD)] - Spielberg, Steven, 1946-; Watts, Robert, 1938-; Ford, Harrison, 1942-; Capshaw, Kate; Puri, Amrish; Seth, Roshan, 1942-; Stone, Philip, 1924-2003; Qiao, Hong, 1927-1999; Quan, Kế Huy, 1971- (Paramount Home Entertainment, 2008)
Indiana Jones, his sidekick Short Round, and nightclub singer Willie Scott go from high-flying action above the Himalayas to a nail-biting runaway mine car chase and finally a spine-tingling escape from a fortress-like mine in India while on the trail of a sacred stone.